THE INTERNATIONAL SCIENTIFIC CONFERENCE "LANGUAGE AS A SYSTEM AND OCCUPATION- 4", DEDICATED TO THE 95TH ANNIVERSARY OF VVEDENSKAYA LYUDMILA ALEKSEEVNA (Rostov-on-Don, October 3-6, 2013) (Proceedings of Southern Federal University. Philology, 2013)
Kashaeva E.Y., Roshanskaya N.D.Keywords: Vvedenskaya L.A., the problem of the theory and history of the language, report, efficiency, importance.This article describes the International scientific conference "Language as a system and occupation - 4". The conference was dedicated to the memory of Vvedenskaya L.A. – a famous linguist, lexicographer, honored professor. Problems of theory and history of the language, lexicology, phraseology, lexicography, sociolinguistics, text interpretation were discussed. Vvedenskaya L.A. made a great contribution to the development of the Russian school of rhetoric, as well as in the creation of scientific, methodological and educational literature on public speaking and culture of speech.